Live‐cell fluorescence imaging reveals dynamic production and loss of bacterial flagella. Issue 2 (2nd May 2020) - Zhuang, Xiang‐Yu; Guo, Shihao; Li, Zhuoran; Zhao, Ziyi; Kojima, Seiji; Homma, Michio; Wang, Pengyuan; Lo, Chien‐Jung; Bai, Fan
Abstract: Bacterial flagella are nanomachines that drive bacteria motility and taxis in response to environmental changes. Whether flagella are permanent cell structures and, if not, the circumstances and timing of their production and loss during the bacterial life cycle remain poorly understood. Here we used the single polar flagellum of Vibrio alginolyticus as our model and implementing in vivo fluorescence imaging revealed that the percentage of flagellated bacteria (PFB) in a population varies substantially across different growth phases. In the early‐exponential phase, the PFB increases rapidly through the widespread production of flagella. In the mid‐exponential phase, the PFB peaks at around 76% and the partitioning of flagella between the daughter cells are 1:1 and strictly at the old poles. After entering the stationary phase, the PFB starts to decline, mainly because daughter cells stop making new flagella after cell division. Interestingly, we observed that bacteria can actively abandon flagella after prolonged stationary culturing, though cell division has long been suspended. Further experimental investigations confirmed that flagella were ejected in V. alginolyticus, starting from breakage in the rod. Our results highlight the dynamic production and loss of flagella during the bacterial life cycle. Importance: Flagella motility is critical for many bacterial species. The bacterial flagellum is made up of about 20 different types of proteins in its final structure and can be self‐assembled. The current understanding of the lifetime and durability of bacterial flagella is very limited. In the present study, we monitored Vibrio alginolyticus flagellar assembly and loss by in vivo fluorescence labeling, and found that the percentage of flagellated bacteria varies substantially across different growth phases. The production of flagella was synchronized with cell growth but stopped when cells entered the stationary phase. Surprisingly, we observed that bacteria can actively abandon flagella after prolonged stationary culturing, as well as in the low glucose buffering medium. We then confirmed the ejection of flagella in V. alginolyticus started with breakage of the rod. Our results highlight the dynamic production and loss of flagella during the bacterial life cycle. Abstract : In the present study, we monitored Vibrio alginolyticus flagellar assembly and loss by in vivo fluorescence labeling, and found that the percentage of flagellated bacteria varies substantially across different growth phases. The production of flagella was synchronized with cell growth but stopped when cells entered the stationary phase. Surprisingly, we observed that bacteria can actively abandon flagella after prolonged stationary culturing, as well as in the low glucose buffering medium.